2016
DOI: 10.1111/pbi.12552
|View full text |Cite
|
Sign up to set email alerts
|

The secretion of the bacterial phytase PHYUS417 by Arabidopsis roots reveals its potential for increasing phosphate acquisition and biomass production during co‐growth

Abstract: SummaryPhytic acid (PA) is a major source of inorganic phosphate (Pi) in the soil; however, the plant lacks the capacity to utilize it for Pi nutrition and growth. Microbial phytases constitute a group of enzymes that are able to remobilize Pi from PA. Thus, the use of these phytases to increase the capacity of higher plants to remobilize Pi from PA is of agronomical interest. In the current study, we generate transgenic Arabidopsis lines (ePHY) overexpressing an extracellular form of the phytase PHY‐US417 of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 55 publications
1
12
0
Order By: Relevance
“…Similarly, expression of B. subtilis 168phyA phytase in A. thaliana led to a higher shoot dry weight and an increase in phosphorus content by 100% compared to the wild type ( Lung et al, 2005 ). Similar results have more recently been obtained with a related BPP phytase PHY-US417 expressed in A. thaliana ( Belgaroui et al, 2014 , 2016 ).…”
Section: Introductionsupporting
confidence: 89%
See 3 more Smart Citations
“…Similarly, expression of B. subtilis 168phyA phytase in A. thaliana led to a higher shoot dry weight and an increase in phosphorus content by 100% compared to the wild type ( Lung et al, 2005 ). Similar results have more recently been obtained with a related BPP phytase PHY-US417 expressed in A. thaliana ( Belgaroui et al, 2014 , 2016 ).…”
Section: Introductionsupporting
confidence: 89%
“…Most of such phytases used in transgenic research are members of the HAP type of phytases ( Pen et al, 1993 ; Verwoerd et al, 1995 ; Brinch-Pedersen et al, 2000 ; Ponstein et al, 2002 ; Hong et al, 2004 ; Bilyeu et al, 2008 ; Wang et al, 2013 ). In addition, a few studies reported successful use of BPP phytases ( Yip et al, 2003 ; Lung et al, 2005 ; Chan et al, 2006 ; Belgaroui et al, 2014 ; Belgaroui et al, 2016 ) and PAP enzymes ( Xiao et al, 2005 ; Ma et al, 2009 , 2012 ). TTP phytases, which represent a relatively rare family of phytases found mostly in ruminant bacteria ( Yanke et al, 1998 ), have also been utilized ( Hong et al, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Plant growth and productivity can be hindered by low availability of phosphorus (P) in the soil [ 14 ]. Therefore, plants have developed mechanisms to improve soil phosphorus availability, with emphasis on the participation of purple acid phosphatases (PAPs).…”
Section: Introductionmentioning
confidence: 99%